Endemic and Emerging Arboviruses in Domestic Ruminants in East Asia - Yanase, Tohru; Murota, Katsunori; Hayama, Yoko (Frontiers in Veterinary Science, 2020)
Epizootic congenital abnormalities caused by Akabane, Aino, and Chuzan viruses have damaged the reproduction of domestic ruminants in East Asia for many years. In the past, large outbreaks of febrile illness related to bovine ephemeral fever and Ibaraki viruses severely affected the cattle industry in that region. In recent years, vaccines against these viruses have reduced the occurrence of diseases, although the viruses are still circulating and have occasionally caused sporadic and small-scaled epidemics. Over a long-term monitoring period, many arboviruses other than the above-mentioned viruses have been isolated from cattle and Culicoides biting midges in Japan. Several novel arboviruses that may infect ruminants (e.g., mosquito- and tick-borne arboviruses) were recently reported in mainland China based on extensive surveillance. It is noteworthy that some are suspected of being associated with cattle diseases. Malformed calves exposed to an intrauterine infection with orthobunyaviruses (e.g., Peaton and Shamonda viruses) have been observed. Epizootic hemorrhagic disease virus serotype 6 caused a sudden outbreak of hemorrhagic disease in cattle in Japan. Unfortunately, the pathogenicity of many other viruses in ruminants has been uncertain, although these viruses potentially affect livestock production. As global transportation grows, the risk of an accidental incursion of arboviruses is likely to increase in previously non-endemic areas. Global warming will also certainly affect the distribution and active period of vectors, and thus the range of virus spreads will expand to higher-latitude regions. To prevent anticipated damages to the livestock industry, the monitoring system for arboviral circulation and incursion should be strengthened; moreover, the sharing of information and preventive strategies will be essential in East Asia.